(3MGTjI Ydi TQM GdLZejfis - (3eMehO Hf eMeO, GHf bGVj RGOg hjbGd dg (B((3ejQe LdHj(B) (3,J (B931 (3g` s
(3ChdgG (B:s
(3Jfejb hJYdjb Ydi LZejfi dOi bhdg GQJaGY GYXe GdLHGd Edi bWQ GdCQV s
(3BNQgG (B:s
(3aEfi HYO GdGYJQGa HGdYLR hGdbUhQ dYdi LfGM GdJQOO ai eSfO JaGhJ GdcShQ dYdge jTahf Ydjc GdUOhQ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdQGHYs
(3GfXQg eY GdeNWhW Qbe (B117s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B183 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B195s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI WgQGf (B(3 / 2417) s
Keywords: (3GdQjGVjGJs